Proposta de um modelo hesitant fuzzy para seleção de prestadores de serviços de manutenção - Santos, Vanessa dos (2024)
Industrial maintenance plays a strategic and fundamental role in organizations, ensuring the availability, reliability and safety of equipment and facilities. Hiring specialized maintenance service providers provides access to up-to-date technical skills and abilities. In the hiring process, it is essential to have the participation of specialists responsible for establishing requirements and selection criteria and evaluating the capabilities of potential service providers. To deal with the uncertainty inherent in this decision-making process, this paper proposed a model for evaluating and selecting industrial maintenance service providers, with the combined application of the Hesitant Fuzzy Linguistic QFD (Quality Function Deployment) and Hesitant Fuzzy Linguistic TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) techniques. Using Microsoft Excel® software, the computational implementation of the model was carried out, followed by the simulated application in a real case in a railway logistics company. In this application, three professionals from the company participated, who, following the model, defined the requirements and criteria and evaluated four alternatives of railway maintenance service providers. The results obtained indicated that mobilization time and productivity were the requirements that received the greatest importance in the evaluation process. Regarding the criteria, the greatest weights were attributed to service reliability, willingness to invest in new equipment, safety training and efficiency. Among the four alternatives of service providers considered in the application, A3 and A1 were the best classified. The decision makers consulted confirmed the effectiveness of the model, which was reinforced by the sensitivity analysis. The proposed model is presented as a practical and flexible tool to support managers in selecting maintenance service providers. It allows for the selection of criteria according to the specific needs of the company or project, and is capable of supporting group decision-making processes in uncertain environments and situations where decision-makers may hesitate. Unlike the previous similar models identified, the proposed model allows the use of linguistic expressions and the incorporation of a pessimistic or optimistic perspective in the decision-making process. The model contributes to the study of the development of management technologies, promoting the improvement of innovation and decisionmaking processes that impact organizational development, in accordance with the objectives of the organizational development research line of the Postgraduate Program in Administration at the Federal Technological University of Paraná.